2000
DOI: 10.1074/jbc.275.10.7144
|View full text |Cite
|
Sign up to set email alerts
|

A Role for Phospholipase D in GLUT4 Glucose Transporter Translocation

Abstract: Based on recent studies showing that phospholipase D (PLD)1 is associated with intracellular membranes and promotes membrane budding from the trans-Golgi, we tested its possible role in the membrane trafficking of GLUT4 glucose transporters. Using immunofluorescence confocal microscopy, expressed Myc epitopetagged PLD1 was found to associate with intracellular vesicular structures by a mechanism that requires its N-terminal pleckstrin homology domain. Partial co-localization with expressed GLUT4 fused to green… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
56
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(64 citation statements)
references
References 61 publications
(66 reference statements)
8
56
0
Order By: Relevance
“…In addition, SWAP-70, a PtdIns(3,4,5)P 3 -dependent guanine nucleotide exchange factor (GEF) for Rac, can regulate membrane ruffling induced by epidermal growth factor (EGF) or PDGF (Shinohara et al, 2002). Although it was reported that the inhibition of PI3K activity results in the downregulation of PLD activity (Emoto et al, 2000;Kozawa et al, 1997;Standaert et al, 1996), the mechanism involved is unknown. Our finding that the PLD1 PX domain has affinity for PtdIns(3,4,5)P 3 is an important clue.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, SWAP-70, a PtdIns(3,4,5)P 3 -dependent guanine nucleotide exchange factor (GEF) for Rac, can regulate membrane ruffling induced by epidermal growth factor (EGF) or PDGF (Shinohara et al, 2002). Although it was reported that the inhibition of PI3K activity results in the downregulation of PLD activity (Emoto et al, 2000;Kozawa et al, 1997;Standaert et al, 1996), the mechanism involved is unknown. Our finding that the PLD1 PX domain has affinity for PtdIns(3,4,5)P 3 is an important clue.…”
Section: Discussionmentioning
confidence: 99%
“…GLUT4 is a recycling receptor that interacts with both AP-1 and AP-2 and recycles to a trans-Golgi network 38-negative compartment (33). Furthermore, PLD activity has also been implicated in translocation of GLUT4 to the PM (34). Perhaps most interestingly, both CTLA-4 and GLUT4 appear to use a storage compartment from which exocytosis is achieved rapidly upon stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to PI3K, PLD is regulated by RalA, a downstream target of Ras, in plateletderived growth factor-and epidermal growth factor-stimulated cells (49,50), and PLD2 is tyrosine-phosphorylated by forming a physical complex with the epidermal growth factor receptor (51). Recent studies have demonstrated that PLD1 and PI3K play a role in GLUT4 translocation between the plasma membranes and intracellular vesicles in insulin-stimulated cells (52). Furthermore, several studies have demonstrated through the use of PI3K inhibitors that PI3K is involved in agoniststimulated PLD activation (53)(54)(55)(56).…”
Section: S1p-induced Phospholipase D Activation In Edg3-over-expressimentioning
confidence: 99%